Agronomic and grain quality traits of oat germplasm in winter fallow fields of Sichuan, China - Xie, Hongying; Zhang, Jing; Ling, Zihan; Tang, Ganqin; Wan, Qiuhong; Zhu, Lijun; Yan, Qiujie; Wu, Qinggui (Frontiers in Plant Science, 2025)
IntroductionTo improve the rate of utilization of idle fields in winter and identify suitable varieties for planting, production, utilization, and oat crop quality, six oat varieties were randomly selected, and their agronomic traits were measured.MethodsSoluble sugars, crude starch, γ-aminobutyric acid, and the content of four types of phenolic nutrients were determined using anthrone, GOPOD oxidase, UV-visible spectrophotometry, Folin-Ciocalteau methods, followed by correlation analysis, respectively. The variety Challenger showed the best growth as measured by the three morphological indices (plant height, leaf width, and stem diameter).ResultsFor the three yield indices (fresh weight, thousand grain weight, and dry weight), the yield of Mengyan 1 and Tianyan 70 was highest and lowest, respectively. The soluble sugar content of Baylor 2 was 5.300%, which was significantly different to the other varieties, and the crude starch content of Baylor 2 was 15.044 mg/g, which was significantly higher than that of the other varieties. The GABA content of Mengyan 1 was 0.220%, which was significantly higher than that of the other varieties. The phenol content of Challenger and Qingyan 1 was significantly higher than that of the other varieties, (1.240 mg/g and 1.100 mg/g respectively), and Challenger had the highest compared with the remaining varieties. Challenger exhibited the best production performance, as determined by a comprehensive evaluation using a gray system correlation analysis, followed by Baylor 2.DiscussionThe preliminary judgment is that Challenger and Baylor 2 can be promoted as the main varieties to plant in idle winter fields in the Mian-Yang area of Sichuan Province, China.